Changes in the Activities of Antioxidant Enzymes in the Fat Body and Hemolymph of Apis mellifera L. Due to Pollen Monodiets - Maciej Sylwester Bryś; Krzysztof Olszewski; Maciej Bartoń; Aneta Strachecka (Antioxidants)
The increasing prevalence of monocultures has reduced floral diversity, diminishing pollen diet variety for bees. This study examines the impact of monofloral pollen diets (hazel, rapeseed, pine, buckwheat, Phacelia, goldenrod) on the antioxidant enzyme activities in the fat body from tergite 3, tergite 5, sternite, and hemolymph of honey bees. We show that pollen from plants such as rapeseed, Phacelia, buckwheat, and goldenrod (rich in phenolic compounds and flavonoids) increases the activities of SOD, CAT, GST, and GPx in the fat body and hemolymph compared to the control group. Although it is commonly known that a monodiet is one of the stress factors for bees, the increase in the activities of these enzymes in the hemolymph and fat body of workers fed with pollen candy compared to those fed only sugar candy has a positive (although inconclusive) effect. These activities in the hemolymph and fat body of bees fed with pollen from anemophilous plants are usually lower compared to those in bees fed with candy containing 10% pollen from rapeseed, Phacelia, buckwheat, or goldenrod. Further research is needed to fully understand the complex interactions among monofloral pollen diets, antioxidant enzyme activities, and the overall physiology of honey bees.